Hellenism and the formation of Coptic identity : 332BCE - 200CE : a Coptic trajectory through a Hellenistic context - Evans, Annette Margeretha Henrietta (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1999.